Peran Orang Tua dalam Menumbuhkan Sikap Tanggung Jawab Belajar Siswa Selama Pembelajaran Daring di MTs Insan Sejati Bogor - Khoirunnisa Harahap; Oking Setia Priatna; Sutisna Sutisna (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The role of parents is very important in fostering an attitude of responsibility for children's learning. Seeing the current situation caused by the emergence of the corona virus (Covid-19) in 2020, the world has experienced many changes and bad impacts. This virus has affected the state of the economy to the point of changing face-to-face learning patterns to distance learning or commonly called online. This study uses a qualitative method with a descriptive analysis approach. This study aims to determine the role of parents in fostering a responsible attitude to student learning during online learning. Data was collected by observation, interviews and documentation. The researcher met 3 respondents, namely the parents of the students of Mts Insan Sejati Bogor. Researchers conducted this research at Mts Insan Sejati Bogor, which was carried out for one month. The results of the study show that parents at Mts Insan Sejati Bogor have played a role in fostering an attitude of learning responsibility for students during online learning. Thus parents have a very big role to increase the sense of responsibility for children's learning. Keywords: Role; Parents; Responsibility; Online Learning